Contribution of ATM and FOXE1 (TTF2) to risk of papillary thyroid carcinoma in Belarusian children exposed to radiation. Issue 7 (15th October 2013) - Damiola, Francesca; Byrnes, Graham; Moissonnier, Monika; Pertesi, Maroulio; Deltour, Isabelle; Fillon, Aurélie; Le, Florence; Tenet, Vanessa; McKay‐Chopin, Sandrine; McKay, James D.; Malakhova, Irina; Masyakin, Vladimir; et al.
<x xml:space="preserve">Abstract</x> A dramatic increase in the incidence of papillary thyroid carcinoma (PTC) after childhood exposure to ionizing radiation from the Chernobyl nuclear accident has been described as the largest number of tumors of one type due to one cause that have ever occurred. inter‐individual variations in response to radiation have been documented and the role of genetics in sporadic PTC is well established, suggesting that genetic factors may also affect the risk of radiation‐related PTC. To investigate how environmental and host factors interplay to modify PTC risk, we genotyped 83 cases and 324 matched controls sampled from children living in the area contaminated by fallout from the Chernobyl power plant accident for 19 polymorphisms previously associated with PTC, thyroid biology or radiation‐induced second primary tumors. Significant association with PTC was found for rs1801516 (D1853N) in ATM (odds ratio (OR) = 0.34, 95% confidence interval (CI) 0.16, 0.73) and rs1867277 in the promoter region of FOXE1 (OR = 1.55, 95% CI 1.03, 2.34). Analysis of additional polymorphisms confirmed the association between these two genes and PTC. Our findings suggest that both DNA double‐strand break repair pathway and thyroid morphogenesis pathway or dysregulation of thyroid differentiated state maintenance are involved in the etiology of PTC, and that the studied genetic polymorphisms and radiation dose appear to act as independent multiplicative risk factors for PTC.